Silver-catalyzed direct regioselective phosphonation of β-aryl-α, β-unsaturated carbonyl compounds with H-phosphites under microwave irradiation. Issue 22 (2nd June 2016) - Yuan, Jin-Wei; Li, Yuan-Zhe; Mai, Wen-Peng; Yang, Liang-Ru; Qu, Ling-Bo
Abstract: An efficient protocol for silver-catalyzed direct radical phosphonation of β-aryl-α, β-unsaturated carbonyl compounds with H -phosphites to afford trans -substituted alkenylphosphonates under microwave irradiation is described. Some notable features of this method are high efficiency, good yield, broad functional groups tolerance, commercially available and cheap catalyst. Graphical abstract: An efficient protocol for silver-catalyzed direct radical phosphonation of β-aryl-α, β-unsaturated carbonyl compounds with H -phosphites to afford trans -substituted alkenylphosphonates under microwave irradiation is described.